Religiosity and emotional sphere of the personality - Yaroschuk, Marianna (Psychological Prospects Journal, 2017)
The paper highlights the results of theoretical and empirical study of individual religiosity and its relation to his/her emotional sphere. Religiosity, as it has been revealed, is an individual feature associated with low depression rate, psychological well-being, positive social attitudes, decreased risk of divorce, better interpersonal relations in family. The search for sense, establishing control, avoiding anxiety, social solidarity and identity formation, individual self-development are among the main aspects of individual religiosity. The results of the empirical investigation have shown that college students who possess all levels of connotative meaning encounter emotional challenges in building interpersonal interaction ties. However, some aspects of these challenges are differently manifested in students who assessed connotitavely the concept of ‘God’. The author substantiated that connotative meanings express individual primary religious experience that determines future dynamics of religiosity as a personal feature. The students with high rates of connotative meaning as contrasted to those with medium and low rates showed lower indices on the scales of inability to control own emotions, dominance of negative emotions, non-flexibility, poor emotions. Primary emotional experience in attitude to God as a basis for individual religiosity development had positive impact on human emotions and effective interpersonal interaction. Further research should be undertaken to investigate the religiosity and other personal states and properties, its general impact on student’s quality of life.